Studi Laju Pembentukan Biogas Dan Komposisi Biogas Pada Digester Bertingkat (Studi Kasus Perbandingan Digester Tingkat 1 Dan 4) - Pradnyana, Widya; Nindhia, Tjokorda Gde Tirta; Adnyana, I W. Bandem (Teknik Desain Mekanika; Vol 10 No 4 (2021): Oktober 2021 : Teknik Desain Mekanika, 2021)
Abstract In the current era, energy and fuel have become very important needs of the people. The supply for energy and fuel is still dominated by non-renewable fossil energy sources, namely oil, coal and natural gas. Therefore, alternative energy that is environmentally friendly and has a renewable source is needed, namely biogas. To produce biogas, a biogas reactor (digester) is needed which is an airtight installation so that the decomposition process of organic matter will run optimally. There are several types of biogas digesters that are raised, including the Fixed-Dome plant digester, Floating Drum plant, and Baloon plant. The results of this study indicate that the biogas production produced from the digester level 1 (first) is 993 liters and the digester level 4 (fourth) is 728 liters for 30 days. After that on the first day until the last day the digester level 1 (first) got the highest biogas content on day 25 as much as CH4 = 75%, CO2 = 25%. Then on the first day until the last day the digester level 4 (fourth) gets the highest biogas content on day 25 as much as CH4 = 75%, CO2 = 25%. Keywords : Multilevel Digester, Livestock Manure, Biogas